(untitled) (Proceedings of the International Conference on Education, 2021)
As an educational innovation, Gamification is a process where the teaching-learning process integrates the principles of playfulness and games, motivating participation in a safe environment that permits mistakes without consequences. As a professional professors it was detected that the students assume, under the managerial concept, that as leaders, they are the ones who should give the orders, are responsible for the project, and in charge of others. With gamification, it is intended that they understand that as leaders, they form networks of teams with mutual interests (Draft and Lane, 2018). This raises the following question: Could gamification be the innovation that ensures students develop leadership skills and collaborative work? During the August-December semester of 2020, the game named ´Ñu da meya was designed and implemented where students taking two courses with little similarity helped each other in a fictitious customer-supplier working relationship where each student played a role to reach a common goal. The role play consists of one Fun Quest and five stages: Preparation, Brief, Script, Negotiation and the Master stage. Through the game ’Ñu da meya, the students acquired knowledge through active learning. They developed the necessary leadership that allowed them to take the initiative in any field, challenge paradigms, and make things happen, ethically. This document shows how through gamification the students develop some competences and discover the value of leadership and collaborative work in realistic scenarios, where each of the participants played a role contributing to collaborative work, problem-solving, leadership, communication and decision-making in a shared environment of commitment. The importance of this project is understanding what makes teamwork efficient at the university level and for students’ discovering the value of leadership and collaborative work and how to exercise them. This project demonstrates the tangible benefits of collaboration between different schools to perform multidisciplinary work